Immunogenicity of transfer RNA isolated from a two-heptose rough mutant of Salmonella typhimurium LT2 in mouse typhoid infection. - Kita, E (1983)
Transfer ribonucleic acid (tRNA) was isolated from a two-heptose mutant of Salmonella typhimurium LT2 (strain SL1004) and was found to afford 100% mouse protection against challenge with 1000 LD50 of strain LT2. The intraperitoneal minimum effective dose of tRNA was 5 micrograms RNA per mouse and this dose was significantly lower than that of ribosomal RNA for ddY mouse strain. The protective immunity was independent of the presence of antibodies to cell-surface antigens, and was transferred mainly by T cells. The protective moiety of tRNA was sensitive to ribonuclease digestion which resulted in 85% reduction in the mouse survival rate, but was completely resistant to protease digestion. The present study demonstrates that the immunogenic activity of salmonella RNA is present in both ribosomal RNA and tRNA.